2011
DOI: 10.1002/lary.22438
|View full text |Cite
|
Sign up to set email alerts
|

Complications and legal outcomes of tonsillectomy malpractice claims

Abstract: Tonsillectomy carries a large amount of risk from a malpractice standpoint. Postoperative bleeding is the complication most commonly associated with malpractice claims, but may not carry the greatest overall risk from a patient care or monetary standpoint. Hypoxic and anoxic events, although less common, appear to carry more morbidity for the patient and are associated with greater settlements and judgments in malpractice claims. Tonsillectomy continues to carry a significant mortality risk, albeit infrequent,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
37
0
3

Year Published

2012
2012
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(42 citation statements)
references
References 28 publications
2
37
0
3
Order By: Relevance
“…This is consistent with other study [63]. The rate of post operative bleeding of 2.88% in the present study was in agreement to the rate of 2.4% found in other studies [64].…”
Section: Discussionsupporting
confidence: 94%
“…This is consistent with other study [63]. The rate of post operative bleeding of 2.88% in the present study was in agreement to the rate of 2.4% found in other studies [64].…”
Section: Discussionsupporting
confidence: 94%
“…(4) Complications are often underreported by surgeons (fear of being reprimanded or litigation) or journals (considered uninteresting). This statement is supported by the surprisingly high number of litigations resulting from tonsillectomy [22,23] which is not mirrored by an adequate amount of reports in the medical literature. (5) There is no uniformly accepted method of performing tonsillectomy.…”
Section: Discussionmentioning
confidence: 64%
“…3,21,29,35,37 Mortality rates of AT have been estimated between 1 in 16 000 and 1 in 35 000 cases. 42 Nixon et al 22 demonstrated that sleep-related airway obstruction is a common postoperative complication leading to significant oxyhemoglobin desaturations after AT in children with severe OSA. Episodes of desaturation occurred during the first postoperative night in all 10 children studied, and these desaturation episodes were predominantly caused by upper airway obstruction.…”
Section: Figurementioning
confidence: 99%